A review of the use of next generation sequencing methodologies to identify biomarkers of resistance to CDK4/6 inhibitors in ER+/HER2- breast cancer. (January 2021) - Servetto, Alberto; Napolitano, Fabiana; De Angelis, Carmine; De Placido, Pietro; Giuliano, Mario; Arpino, Grazia; De Placido, Sabino; Bianco, Roberto; Formisano, Luigi
Highlights: CDK4/6 inhibitors revolutionized the treatment of ER + breast cancer. NGS methodologies identified several mechanisms of resistance to CDK4/6 inhibitors. Major limitation of DNA-NGS preclude its routine clinical application. Genomic alterations are not the only mechanisms of resistance to CDK4/6 inhibitors. Gene expression analysis will further elucidate this composite scenario. Graphical abstract: Abstract: The development of cyclin-dependent kinases (CDK) 4 and 6 inhibitors represented a substantial breakthrough in the treatment of estrogen receptor positive (ER+), human epidermal growth factor receptor 2 (HER2) negative metastatic breast cancer. These drugs showed a significant clinical benefit in pivotal clinical trials. However, resistance eventually occurs, leading to disease progression. Next Generation Sequencing methodologies have been employed to investigate predictive biomarkers of response or resistance to CDK4/6 inhibitors. Whole exome and targeted sequencing of solid and liquid biopsies have revealed several possible genomic alterations associated with resistance. Notably, genomic alterations identified by DNA-sequencing did not fully recapitulate the entire landscape of resistance to CDK4/6 inhibitors. Gene expression analysis, such as RNA-Seq methodologies, have provided insights into transcriptional profiles and may need further application. Herein, we report the main findings derived from the use of NGS analysis in the context of resistance to CDK4/6 inhibitors in ER + breast cancer.